Excelentíssima ministra: um olhar sobre a representatividade feminina no STF à luz do Constitucionalismo Feminista - FURTADO, Monalisa de Miranda (2024)
The follow study results from a research on the foundational process of the Brazilian Supreme Court as a product based on liberal and patriarchal constructs which, systematically, generates the perpetuation of the silence to a part of the population, given the underrepresentation of women in the court, especially on its intersectional view, as a fact that contributes to one-dimensional, androcentric and white ways of decisions and interpretations, disconnected from social reality. The following paper objective is to quantitatively analyze the female occupation in the Brazil constitutional court, considering aspects as gender and race, as well as the progress brought by the inclusion of womens in jurisdictional instances of power, aiming to understand in what extent the representation of women in the Supreme Court contributes to the consolidation of feminist constitutionalism and to the strengthening of the democratic institutions in Brazil, as well as questioning whether the lack of diversity in the composition of the Court contributes to a stagnation in debates on gender and racial justice, leading to a possible compromisation of its legitimacy.